Diversidade taxonômica e funcional das assembleias de peixes em estuários tropicais com gradientes salinos distintos: estuário positivo e hipersalino - Silva, Genielyson Pereira (2023)
Estuarine ecosystems are among most dynamic and productive in world. Because are located in a transition zone, these environments will present a high heterogeneity of habitats which provide fish species find effective refuges against predators, places for feeding and establishment. These characteristics will directly influence in taxonomic and functional diversity of fish assemblages. The present study aims analyze taxonomic and functional diversity indices in two tropical estuaries with distinct saline gradients, the Tubarão River estuary - RN (inverse/negative) and Mamanguape River estuary - PB (positive). For this, four habitats were selected in each estuary: two structured with presence of vegetation and two unstructured without presence of vegetation, respectively seagrass (BF), mangrove (FM), mudflat (PL) and sandflat (PA). Samplings were carried out between 2012 and 2014, standardized and with the same fishing gear, where trawls were carried out perpendicular to border with duration of 3 min. The ichthyofauna collected in two estuaries presented a total of 43,957 individuals, of these, 18,544 were collected in the Tubarão River estuary, 25,431 were collected in Mamanguape River estuary. To verify the different indices of taxonomic diversity, the Shannon diversity indices (H') were calculated, which showed a significant difference (p<0.05) for both estuaries. Testing Pielou's equitability (J'), it was found that there wasn't significant difference for any of estuaries. With regard to functional diversity indices, functional richness (FRic), functional uniformity (FEve) and functional divergence (FDiv) were tested, and only functional richness (FRic) was significant (p<0.05). Four functional attributes were also selected: diet, vertical habitat, body shape and caudal fin shape, where community weighted average (CWM) values showed dominant functional traits had the greatest influence, for Tubarão estuary were fin furcada, compressiform body, zooplanktivores and zoobenthivores species. As for Mamanguape estuary, they were furcated fin, zoobentivores, fusiform body, benthopelagic, compressiform body and zooplanktivores species. This study showed that taxonomic and functional diversity is influenced by associated habitats and saline gradient of estuaries. These characteristics are important to guarantee potential nursery areas, estuarine diversity and ecological integrity, directly contributing to management, conservation and handling of estuarine ecosystems.